STUDENTS EXPECTATIONS TOWARD THEIR TEACHERS: A STUDY ON TEACHERSâ COMPETENCE, GENDER ISSUES AND POLITENESS BETWEEN TEACHERS AND STUDENTS IN INDONESIAN CONTEXT - Mahmud, Murni (ELT WORLDWIDE, 2015)
This paper depicts the studentsâ perception on the ways their teachers teach them. There were 80 respondents involved in this research consisting 40 students from undergraduate and 40 students from graduate program. The respondents are the English students of the Graduate and undergraduate Program of the State University of Makassar. An open ended questionnaire was distributed to them to reveal their perception towards their teachersâ teaching styles. The findings of this research revealed expectations from students towards their teachers in terms of the use of materials and methods in the class, the classroom interaction and management by the teachers, and the teachersâ personal identities. Some other aspects such as gender relation and politeness were taken into consideration on the studentsâ preferences.